Screening chelating inhibitors of HIF-Prolyl Hydroxylase Domain 2 (PHD2) and Factor Inhibiting HIF (FIH) - Flagg, Shannon C. (2012)
Two primary O(2)-sensors for humans are the HIF-hydroxylases, enzymes that hydroxylate specific residues of the hypoxia inducible factor-α (HIF). These enzymes are factor inhibiting HIF (FIH) and prolyl hydroxylase-2 (PHD2), each an α-ketoglutarate (αKG) dependent, nonheme Fe(II) dioxygenase. Although the two enzymes have similar active sites, FIH hydroxylates Asn(803) of HIF-1α while PHD2 hydroxylates Pro(402) and/or Pro(564) of HIF-1α. The similar structures but unique functions of FIH and PHD2 make them prime targets for selective inhibition leading to regulatory control of diseases such as cancer and stroke. Three classes of iron chelators were tested as inhibitors for FIH and PHD2: pyridines, hydroxypyrones/hydroxypyridinones and catechols. An initial screen of the ten small molecule inhibitors at varied [αKG] revealed a non-overlapping set of inhibitors for PHD2 and FIH. Dose response curves at moderate [αKG] ([αKG] ~ K(M)) showed that the hydroxypyrones/hydroxypyridinones were selective inhibitors, with IC(50) in the µM range, and that the catechols were generally strong inhibitors of both FIH and PHD2, with IC(50) in the low µM range. As support for binding at the active site of each enzyme as the mode of inhibition, electron paramagnetic resonance (EPR) spectroscopy were used to demonstrate inhibitor binding to the metal center of each enzyme. This work shows some selective inhibition between FIH and PHD2, primarily through the use of simple aromatic or pseudo-aromatic chelators, and suggests that hydroxypyrones and hydroxypyridones may be promising chelates for FIH or PHD2 inhibition.